Characterization and expression analysis of adipokinetic hormone and its receptor in eusocial aphid Pseudoregma bambucicola - Jedličková, Veronika; Jedlička, Pavel; Lee, How-Jing (General and comparative endocrinology, 2015)
Aphids display an extraordinary phenotypic plasticity ranging from widespread reproductive and wing polyphenisms to the occurrence of sterile or subfertile soldier morphs restricted to eusocial species of the subfamilies Eriosomatinae and Hormaphidinae. Individual morphs are specialized by their behavior, anatomy, and physiology to perform different roles in aphid societies at different stages of the life cycle. The capacity of the insects to cope with environmental stressors is under the control of a group of neuropeptides of the adipokinetic hormone/red pigment-concentrating hormone family (AKH/RPCH) that bind to a specific receptor (AKHR). Here, we describe the molecular characteristics of AKH and AKHR in the eusocial aphid Pseudoregma bambucicola. The sequence of the bioactive AKH decapeptide and the intron position in P. bambucicola AKH preprohormone were found to be identical to those in a phylogenetically distant aphid Dreyfusia spp. (Adelgidae). We detected four transcript variants of AKHR that are translated into three protein isoforms. Further, we analyzed AKH/AKHR expression in different tissues and insects of different castes. In wingless females, a remarkable amount of AKH mRNA was only expressed in the heads. In contrast, AKHR transcript levels increased in the order gut<ovary<fat body<head. In aphids from both the primary and secondary hosts (Styrax suberifolia and Bambusa spp., respectively), the highest AKH expression levels were recorded in winged, migratory females and soldiers, whereas reduced levels were found in wingless, sedentary females that are functionally oriented to reproduction. The highest AKHR expression was found in soldiers in gall-dwelling populations, whereas in bamboo colonies the highest transcript level was detected in winged females. We propose a possible explanation for the correlation between AKH and AKHR transcript levels and task partitioning among individual forms in P. bambucicola colonies.
Keywords: RNA, Messenger; sekvence nukleotidů; kvantitativní polymerázová řetězová reakce; Gene expression; fylogeneze; Pseudoregma bambucicola; Phylogeny; hmyzí hormony; hmyzí proteiny; molekulární sekvence - údaje; mšice; Amino Acid Sequence; polymerázová řetězová reakce s reverzní transkripcí; Real-Time Polymerase Chain Reaction; Receptors, Glucagon; Oligopeptides; kyselina pyrrolidonkarboxylová; Pyrrolidonecarboxylic Acid; receptory glukagonu; Adipokinetic hormone; Animals; ženské pohlaví; G-protein coupled receptor; zvířata; Soldier caste; Insect Hormones; Reverse Transcriptase Polymerase Chain Reaction; sekvence aminokyselin; Insect Proteins; Aphids; Molecular Sequence Data; Base Sequence; Female; oligopeptidy; messenger RNA; Eusocial aphids